Strikingly similar: Comparing visual political communication of populist and non-populist parties across 28 countries. (October 2022) - Farkas, Xénia; Jackson, Daniel; Baranowski, Paweł; Bene, Márton; Russmann, Uta; Veneti, Anastasia
Along with the recent boom in support of populist movements in Europe, social media seems to be the ideal place for their interaction with the public. While Facebook has been thoroughly explored for populist campaigning, there is still scarce research on visual aspects of their communication. Analysing the 2019 European Parliament campaign, this study seeks to determine the distinct characteristics of a populist visual communication style and its differences in relation to the non-populist parties. Applying quantitative content analysis to the images ( N = 997) posted on Facebook by political parties from 28 countries enabled us to show that there is a predominance of similarities in both communication styles. Although populists demonstrated a higher propensity to depict their leader and use national symbols, these were exceptions to the overwhelming evidence of uniformity in campaigning methods. Hence, we argue that despite evidence of textual visibility, populist communication does not explicitly manifest through images.